PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA PERUSAHAAN DENGAN KUALITAS SISTEM INFORMASI AKUNTANSI SEBAGAI VARIABEL INTERVENING - Indriani, Milisa; Istutik, Istutik (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
This study aims to examine the effect of information technology utilization on company performance with quality of accounting information system as an intermediate variable. The population of this research is all employees who work in Finna Golf & Country Club as many as 224 employees. Samples in this study were selected by using non probability sampling-purposive sampling. The number of samples are 31 respondents. Data obtained were analized using SmartPLS software version 2.0. The results of this study indicate three findings. First, there is positive effect between utilization of information technology on company performance. Second, there is positive effect between quality of accounting information systemon company performance. Three, there is a positive effect betweenutilization of information technology on quality of accounting information system.